SINTESIS DAN KARAKTERISASI NANOKOMPOSIT KONDUKTIF NANOFIBER - Muhamad Nasir (Research Center for Chemistry - LIPI, 2013)
Conductive composite polyanilinelPVDF nanofiberhas been synthesized by using co-axial electro spinning.Morphology and diameter of nanofiber was influenced byPVDF polymer concentration and the type of solvent. Beadednanofiberwas formed at lower polymer concentration. On thecontrary, free beaded nanofiber was formed at higherpolymer concentration. Result of FTIR analysis showed thatPVDF crystal structure was dominant by p-phase crystalstructure. Conductive composite nanofiber has potentialapplication in sensor, actuator and airfilter.Keywords: Conductive composite nanofiber, co-axialelectrospinning, polyaniline/pvdf compositenanofiber